(untitled) (Tempo e Argumento, 2025)
In recent years, the discussion around decoloniality has advanced in the field of human and social sciences, especially in the field of history. We understand decoloniality as a theoretical movement that is inseparable from praxis (action), and that seeks, among other things, the (re)foundation of Brazilian universities (Carvalho, 2019). In this sense, the rupture with coloniality invariably involves the need to dialogue with the epistemologies formulated by those elevated to the status of “condemned of the earth”. In line with the perspective of decoloniality, this article seeks, based on dialogues with important black theorists, Audre Lorde, bell hooks and Grada Kilomba, to reflect on the importance of breaking with the notion of intellectual forged by coloniality. Starting from the notion that an intellectual is someone who produces counter-hegemonic ideas (bell hooks), the text presents the trajectory of José Correia Leite, one of the greatest exponents of the Brazilian black movement of the 20th century. Based on Leite’s intellectual journey, we revisit important aspects of the struggle carried out by black women and men in Brazil in search of the “new abolition”.